Triniti daripada perspektif Taoisme: analisis pemikiran Jung Young Lee - Zuraiza Husin,; Jaffary Awang, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
Jung Young Lee is a Korean-born theologian who employs creatively the doctrine of the Trinity from an Asian worldview. This article aims to analyze Leeâ€™s approaches of the Trinity with the Yin-Yang symbolism. The main reference is based on the book written by him entitled â€˜The Trinity in Asian Perspective (1996)â€™. Lee has turned his attention to the topic of Trinity through the lens of the culture and thought patterns of his own milieu. One of the leading point in presenting Yin-Yang principle as Trinitarian thinking, Lee examines the interpretation of the term â€œinâ€ in the Bible, "Believe me that I am in the Father and the Father is in me" (John 14:11). The statement leads to the point that Yin and Yang cannot exist without each other because relationality is given priority than individuality. The idea is based on the terminology of â€˜both/andâ€™. So, â€˜andâ€™ indicates a Trinitarian statement, there is interdependence and unification. With reference to Trinity, the Father and the Son are One because of â€˜andâ€™. In addition, the same concept implements to the Holy Spirit. Lee views â€˜andâ€™ is not only a linking principle in both-and thinking but also the principle that is â€˜betweenâ€™ two. When â€˜twoâ€™ exists, the third also exist between them. Based on the idea of â€˜middleâ€™, represents the connecting element between two, which contributes for the existence of the Third. Accordingly, the Spirit is the third element in the Trinity relationship.